2004
DOI: 10.1007/s10152-004-0171-9
|View full text |Cite
|
Sign up to set email alerts
|

Using HPLC pigment analysis to investigate phytoplankton taxonomy: the importance of knowing your species

Abstract: Phytoplankton microscopic enumerations and HPLC analyses of their pigments were performed weekly for a complete year at a coastal station in the English Channel. The taxonomic composition of the phytoplankton community was assessed using the HPLC results combined with the mathematical tool CHEMTAX in two different ways. Firstly, without using the species level taxonomic information obtained at the microscopic level (blind analyses), and secondly by including the information from the microscopic taxonomic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 21 publications
2
45
1
Order By: Relevance
“…(Antajan et al, 2004;Irigoien et al, 2004). We compared the pigment data to microscopic counts (data not shown), as well as to plankton analyses from the mesocosms (Egge et al, 2007;, and found it to be consistent.…”
Section: Generalmentioning
confidence: 70%
“…(Antajan et al, 2004;Irigoien et al, 2004). We compared the pigment data to microscopic counts (data not shown), as well as to plankton analyses from the mesocosms (Egge et al, 2007;, and found it to be consistent.…”
Section: Generalmentioning
confidence: 70%
“…Successful estimates of phytoplankton community structure from pigment data using the CHEMTAX program rely largely on the initial choice of pigment to chl a ratios, which can vary with species (e.g. Jeffrey & Wright 1994, Irigoien et al 2004), irradiance and nutrients (e.g. Goericke & Montoya 1998, Henriksen et al 2002, Rodríguez et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, better agreement between the 2 techniques was found for large diatoms than for small flagellates (Rodríguez et al 2002, Garribotti et al 2003, Llewellyn et al 2005. The discrepancy between the 2 approaches was probably caused by ambiguity of some chemotaxonomic pigments (Irigoien et al 2004), uncertain bio-volume to carbon conversion factors (Montagnes et al 1994), or simply the large variation in carbon-to-chlorophyll ratios among different dominant species and different growth stages.One possible issue that may cause bias and inaccurate estimation of taxon-specific mesozooplankton grazing rates in our approach is the inclusion of fecal materials that contain partially digested pigment in the samples. While recognizing that pigment degradation and alteration are likely to occur in the gut of herbivorous zooplankton and different marker pigments may be degraded to a different extent in the fecal pellets (e.g.…”
mentioning
confidence: 97%
“…Thus derived chl a contribution from the non-diatom ensemble was summed and considered as an additional statistical variable. The CHEMTAX method has previously been shown to underestimate the relative abundances of certain dinoflagellates and haptophytes due to unique pigment markers in some species of these groups (Irigoien et al 2004). Furthermore, dia toms have a higher chl a:C ratio than other phytoplankton, and chl a estimates derived from the Chemtax method may overestimate their biomass (Llewellyn et al 2005).…”
Section: Phytoplankton Community Datamentioning
confidence: 99%